PD-1 blockade with pembrolizumab for classical Hodgkin lymphoma after autologous stem cell transplantation - Armand, Philippe (Blood, 2019)
Autologous stem cell transplantation (ASCT) remains the standard of care for patients with relapsed/refractory (RR) classical Hodgkin lymphoma (cHL) who respond to salvage chemotherapy. However, relapse after ASCT remains a frequent cause of treatment failure, with poor subsequent prognosis. Because cHL is uniquely vulnerable to programmed cell death-1 (PD-1) blockade, PD-1 blockade given as consolidation after ASCT could improve ASCT outcomes. We therefore conducted a multicohort phase 2 study of pembrolizumab in patients with RR cHL after ASCT, hypothesizing that it would improve the progression-free survival (PFS) at 18 months after ASCT (primary end point) from 60% to 80%. Pembrolizumab was administered at 200 mg IV every 3 weeks for up to 8 cycles, starting within 21 days of post-ASCT discharge. Thirty patients were treated on this study. The median age was 33 years, and 90% were high-risk by clinical criteria. Seventy-seven percent completed all 8 cycles. Toxicity was manageable, with 30% of patients experiencing at least 1 grade 3 or higher adverse event (AE), and 40% at least 1 grade 2 or higher immune-related AE. Two patients were lost to follow-up in complete remission at 12 months. The PFS at 18 months for the 28 evaluable patients was 82%, meeting the primary end point. The 18-month overall survival was 100%. In conclusion, pembrolizumab was successfully administered as post-ASCT consolidation in patients with RR cHL, and resulted in a promising PFS in a high-risk patient cohort, supporting the testing of this strategy in a randomized trial. This trial was registered at www.clinicaltrials.gov as #NCT02362997.